Powering the Internet of Things: Advances in Energy Harvesting Technologies - Bhushan Gopala Reddy (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Energy harvesting has emerged as a transformative solution for powering Internet of Things (IoT) devices, offering a sustainable alternative to traditional battery-dependent systems. This article presents a comprehensive analysis of energy harvesting technologies and their integration into IoT applications, examining the fundamental principles, implementation challenges, and real-world deployments. It explores various harvesting methods including photovoltaic, piezoelectric, thermoelectric, and RF energy capture systems, and their respective power management strategies and storage solutions. Through detailed case studies spanning smart agriculture, industrial monitoring, and medical devices, this article demonstrates how energy harvesting techniques can significantly enhance device autonomy and reduce environmental impact. This article also addresses critical challenges in miniaturization, efficiency optimization, and system integration, providing insights into emerging solutions and standardization efforts. It suggests that advances in materials science, coupled with intelligent power management algorithms, are enabling increasingly efficient and reliable self-powered IoT devices. This article contributes to the growing body of research on sustainable IoT implementations and provides a framework for future developments in energy-autonomous sensing systems.